Anti-inflammatory activity exhibited by supercritical fluid extract of aquilaria malaccensis leaves - Eissa, Manar; Hashim, Yumi Zuhanis Has-Yun; Zainurin, Nur Aimi Aliah (2018)
Supercritical fluid extraction (SFE) is a modern and environmentally clean method of extraction that presents various advantages over the conventional extraction methods. SFE was used previously in extracting several plant matrices and the extracts demonstrated various pharmacological effects. In this study, the SFE extract of Aquilaria malaccensis leaf was assessed for its extraction yield and anti-inflammatory effect using albumin denaturation method. The results showed that the yield percentage was 1.255% (wt/wt), and the extract exhibited inhibition of albumin denaturation as an indication of anti-inflammatory response that ranges between (28.835% - 52.477%). The significance of this study is to introduce SFE as an effective alternative to traditional methods in the extraction of bioactive compounds with anti-inflammatory activity from Aquilaria species; which could then be an alternative halal ingredient for nutraceuticals and pharmaceuticals.